2018
DOI: 10.1001/jamasurg.2017.3787
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti–Factor Xa–Guided Dosing of Enoxaparin With Venous Thromboembolism After Trauma

Abstract: Rates of VTE were not reduced with anti-Xa-guided dosing, and almost half of the patients never reached prophylactic anti-Xa levels; achieving those levels did not decrease VTE rates. Thus, other targets, such as platelets, may be necessary to optimize thromboprophylaxis after trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 34 publications
2
67
3
1
Order By: Relevance
“…Moreover, in a study examining the potential antithrombotic benefit of HCQ in patients with anti‐phospholipid syndrome, patients treated with HCQ in addition to standard oral anticoagulant therapy had no increased bleeding events . The trauma literature demonstrates persistently elevated VTE rates despite the use of gold standard therapy via low‐molecular‐weight heparins, suggesting that perhaps targeting the coagulation cascade alone is insufficient in this high‐risk patient population . The addition of platelet inhibition for DVT prophylaxis in trauma has been advocated by some but remains controversial .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in a study examining the potential antithrombotic benefit of HCQ in patients with anti‐phospholipid syndrome, patients treated with HCQ in addition to standard oral anticoagulant therapy had no increased bleeding events . The trauma literature demonstrates persistently elevated VTE rates despite the use of gold standard therapy via low‐molecular‐weight heparins, suggesting that perhaps targeting the coagulation cascade alone is insufficient in this high‐risk patient population . The addition of platelet inhibition for DVT prophylaxis in trauma has been advocated by some but remains controversial .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 The trauma literature demonstrates persistently elevated VTE rates despite the use of gold standard therapy via low-molecular-weight heparins, suggesting that perhaps targeting the coagulation cascade alone is insufficient in this high-risk patient population. 3,4,[58][59][60][61] The addition of platelet inhibition for DVT prophylaxis in trauma has been advocated by some but remains controversial. [61][62][63] Whether HCQ represents a potential VTE thromboprophylaxis strategy in addition to current standard of care warrants further clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical implications of such findings are uncertain. A large retrospective study in trauma patients from North America demonstrated no reduction in VTE with twice daily fractionated heparin dosed to achieve peak anti-Xa levels of 0.2-0.4 IU/ml [18] . In comparison, several other studies in trauma patients, including one prospective cohort study, have demonstrated that prophylactic anti-Xa activity can be achieved by up-titrating doses and that these adjustments were associated with a reduction in DVT [13,15,16] .…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…Moreover, higher empirical dosing (e.g. 30 mg SC enoxaparin BD) may still provide inadequate chemoprophylaxis in many patients, as evidenced by low anti-Xa activity and the development of VTE [12][13][14][15]17,18] .…”
Section: Introductionmentioning
confidence: 99%